2021
DOI: 10.1016/j.ebiom.2021.103728
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide association between EYA1 and Aspirin-induced peptic ulceration

Abstract: Background: Low-dose aspirin can cause gastric and duodenal ulceration, hereafter called peptic ulcer disease (PUD). Predisposition is thought to be related to clinical and genetic factors; our aim was to identify genetic risk factors associated with aspirin-induced PUD. Methods: Patients (n=1478) were recruited from 15 UK hospitals. Cases (n=505) were defined as patients with endoscopically confirmed PUD within 2 weeks of using aspirin and non-aspirin Non-Steroidal Anti-Inflammatory Drugs (NSAIDs). They were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…With H. pylori (HP) infection and the use of non-steroidal anti-inflammatory drugs (NSAIDs) being two of the most common causes of GU and DU 3 , genetic factors also play a critical role in the development of PUD 4 . Previous genome-wide association studies (GWASs) of PUD had identified multiple loci, mainly HP-related, in Europeans 5,6 . Given the relatively high prevalence of PUD and HP infection in East Asians and the remarkably limited number of risk loci identified in East Asian populations 2,7 , GWAS with a larger sample size of EAS ancestry individuals would be required to enhance our understanding of genetic etiology of PUD.…”
mentioning
confidence: 99%
“…With H. pylori (HP) infection and the use of non-steroidal anti-inflammatory drugs (NSAIDs) being two of the most common causes of GU and DU 3 , genetic factors also play a critical role in the development of PUD 4 . Previous genome-wide association studies (GWASs) of PUD had identified multiple loci, mainly HP-related, in Europeans 5,6 . Given the relatively high prevalence of PUD and HP infection in East Asians and the remarkably limited number of risk loci identified in East Asian populations 2,7 , GWAS with a larger sample size of EAS ancestry individuals would be required to enhance our understanding of genetic etiology of PUD.…”
mentioning
confidence: 99%